Redefining the Defensive Line: critical components of the innate immune system - Lauro, Mackenzie L. (ACS Infect Dis, 2016)
The human body harbors over a trillion microorganisms; the innate immune system is charged with a tremendous task, to recognize “the needle in the haystack” or in other words to sense the pathogen in this milieu. In this viewpoint, three recent discoveries in the field of innate immunity are discussed and we highlight how in each case multiple disciplines worked together to expand the elements of the innate immune system.